Diagnosis and Management of Mucormycosis: A Rare Fungal Infection in COVID-19 Patients - Samale, Anuja A.; Rathod, Vimal S.; More, Sanjaykumar R.; Gujrathi, Atish B. (New Advances in Medicine and Medical Science Vol. 6, 2023)
This chapter presents an experience of 90 patients of invasive fungal sinusitis over the past 3 months patients being presenting along with COVID-19 or as a post covid19 sequel. Since the emergence of the COVID-19 pandemic, it has been suspected that mucormycosis might cause signifcant morbidity to infected patients. There are multiple possible contributing factors for the development of mucormycosis among patients with COVID-19 and these include diabetes mellitus, obesity, use of corticosteroid, and the development of cytokine storms. We have studied 90 patients of invasive fungal sinusitis at tertiary care centers over a period of 3 months from March 2021 to June 2021 prospectively. The widespread use of corticosteroids/monoclonal antibodies/broad-spectrum antibiotics as part of the treatment against COVID-19 may lead to the development/exacerbation of pre-existing fungal diseases. A total of 67 males and 23 females of age group 41 to 70 years were presented as cases of invasive fungal sinusitis with suspicion of Mucormycosis. In our study 48 out of 90 (53%) patients need surgical cure. One of these patients was cured by Caldwell Luc surgery. Most of the remaining patients either operated with functional endoscopic sinus surgery (FESS) alone (70%) or combined with Caldwell Luc (12.5%) or maxillectomy (14.5%). With the COVID-19 pandemic, invasive fungal sinusitis, including the formerly uncommon illness mucormycosis, has become much more common. Invasive fungal illnesses are on the rise, and factors include immune dysregulation brought on by COVID-19, diabetes mellitus, and widespread use of corticosteroids and antibiotics are all to blame. Early diagnosis, surgical intervention and antifungal treatment help to reduce mortality and morbidity. A high degree of clinical suspicion is needed to diagnose Mucormycosis and timely aggressive management is necessary to improve outcome in Mucormycosis.